Lipoxin and Resolvin Receptors Transducing the Resolution of Inflammation in Cardiovascular Disease - Pirault, John; Bäck, Magnus (Frontiers in Pharmacology, 2018)
A non-resolving inflammation results in a chronic inflammatory response, characteristic of atherosclerosis, abdominal aortic aneurysms and several other cardiovascular diseases. Restoring the levels specialized proresolving mediators to drive the chronic cardiovascular inflammation towards resolution is emerging as a novel therapeutic principle. The lipid mediators lipoxins and resolvins exert their proresolving actions through specific G-protein coupled receptors (GPCR). So far, four GPCR have been identified as the receptors for lipoxin A4 and the D- and E-series of resolvins, namely ALX/FPR2, DRV1/ GPR32, DRV2/GPR18, and ERV1/ChemR23. At the same time other pro-inflammatory ligands also activate some of these receptors. Recent studies of genetic targeting of these receptors in atherosclerotic mouse strains have revealed a major role for prereolving receptors in atherosclerosis. The present review addresses the complex pharmacology of these four proresolving GPCRs with focus on their therapeutic implications and opportunities for inducing the resolution of inflammation in cardiovascular disease.